Workshop. Armenia-Turkey: lessons and realities (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The workshop, held on March 7, 2022, at the Institute of Oriental Studies of the NAS RA, was devoted to the ongoing Armenian-Turkish negotiations to discuss the factors underlying the fourth attempt to normalize Armenian-Turkish relations. Invited scholars, experts and former diplomats shared with their observations. The researchers tried to answer the questions - What lessons can Armenia draw from its 30-year experience of normalization of relations with Turkey? What scenarios can Armenia explore in the current phase of normalization?
Keywords: Workshop